Evaluasi dan Pengembangan Sistem Informasi Rekam Medis Berbasis Cloud: Transformasi Pelayanan Kesehatan - Sari, Jayanti Yusmah; Bantun, Suharsono; Nirsal, Nirsal (INFORMAL: Informatics Journal, 2023)
The problem that is often encountered in medical record services at the hospital, is that processing registration data is less efficient and effective because it still uses manual bookkeeping as an archive so there are several obstacles such as difficulties in searching patient data and the risk of data redundancy. When the patient does not bring a medical card, there is a risk of damage or loss of patient data, as well as the risk of accumulation of patient data books which require special storage space. Therefore, in this research a medical record information system was built using the waterfall method, which consists of requirements, design, implementation, verification and maintenance. Based on the results of white box testing, the cyclomatic complexity is 27, region = 27 and independent path = 27, which shows the system is running well without errors. Furthermore, UAT (User Acceptance Testing) testing resulted in a percentage of 81.5% from 10 respondents indicating the system received good responses from users.